The Welsh dark bee (Apis mellifera mellifera) is not extinct - Elen, Dylan (2022)
Due to past and present imports of Apis mellifera ligustica (Italian bees), Apis mellifera carnica (Carniolan bees) and the English Buckfast bee (a hybrid strain) across its entire natural range, Apis mellifera mellifera is now threatened with extinction by genetic pollution through hybridization. Whilst the status of remnant A. m. mellifera populations is well documented on the European mainland, few studies have been undertaken to identify surviving populations on the British Isles. A few A. m. mellifera stocks are thought to persist in Scotland and the southwest of England and recently, Ireland might appear to contain multiple non-hybridized A. m. mellifera populations. 163 young worker bees, representing 121 colonies from across Wales, were genetically screened in an attempt to identify remnant A. m. mellifera stocks, as part of a conservation breeding program. Recent studies have demonstrated that honey bees of local origin have significantly higher survival chances than honey bees of non-local origin due to their adaptation to their local environment, suggesting that conservation of locally adapted honey bees is a logistical and practical possibility to develop sustainable apiculture. Within this survey, we made use of a custom-tailored SNP genotype assay to estimate the extent of C lineage introgression in the ncDNA as well as sequencing of the tRNAleucox2 intergenic region of the mtDNA to check for the ancestry of the tested colonies